The History of Micro-Geopolitical Divisions: Divided Cities in Former Yugoslav States - Novak, N. (2021)
The period after the Great War marked significant geopolitical perturbances in Europe. The collapse of empires, (post)colonialism and the rise of communism and other extremist movements, opposed the liberal understandings of free market, democracy and national self-determination. In Southeastern Europe, the idea of shared South Slavic state brought together nations previously engaged on opposite sides in the War. Battles for political and national dominance, hegemony, clashes of different ideas and constant changes of alliances and internal borders of several shared states led towards further micro-geopolitical divisions in this part of the world. Attempts to make the idea of Yugo-Slavism work fostered the processes of reterritorialization and deterritorialization in the region of former Yugoslavia. The ultimate attempt that sought solutions for Yugoslav nations ended up in wars. The last armed conflicts that happened in the European continent in the 20th century were the Civil War in Bosnia and Herzegovina, the Croatian Homeland War and the Kosovo War. Even though these states are now independent and internationally recognized countries, post-crisis management had little success. Recognized national borders did not prevent further divisions on local levels and microscale geopolitics. Divided regions, cities and immaterial ethnic micro-borders still burden lived realities and geopolitical visions in this region. This research is designed as a case study of the micro-geopolitical divisions in the former Yugoslavia with a special focus on divided cities. The primary unit of analysis is microscale entities in the region, but within-case cases are divided cities in states which territories were affected by the Yugoslav Wars – Bosnia and Herzegovina, Croatia and Kosovo. The research combines synchronic and diachronic analysis, as it has historical components and it studies the processes of reterritorialization and deterritorialization in the region – diachronic approach, while, at the same time, it focuses on three similar case studies of the divided cities that were an outcome of those processes – synchronic approach. Those three case studies are Mostar, Vukovar and Kosovska Mitrovica.